Theorizing Human Resource Development Practices in Extended Contexts: Invited Reaction 2. (December 2022) - Yoon, Hyung Joon
The first strength of Wang and Doty's (2022) theorizing of HRD practices is its applicability to both micro and macro HRD practices. With the three components—host institutional system (HIS), shaping, and skilling—both organizational and national HRD practices can be explained. Second, their theorizing makes HRD embrace organization development (OD) more closely. The third strength is that it could be used to discern what HRD is and is not. The primary challenge of the theorizing is a lack of appreciation of human agency exerted by the members and HRD practitioners of a closed HIS. Second, selecting appropriate measures and computing variables for analysis using the proposed mathematical formulations seems too complicated if not impossible. Lastly, the premise of the theorizing of HRD practices—the belief that each human system can be classified as an open or a closed HIS—may not work in many HISs.